2013
DOI: 10.1016/j.vaccine.2013.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Ehrlichia P29 protein induces a protective immune response in a mouse model of ehrlichiosis

Abstract: Ehrlichioses are emerging tick-borne bacterial diseases of humans and animals for which no vaccines are available. The diseases are caused by obligately intracellular bacteria belonging to the genus Ehrlichia. Several immunoreactive proteins of ehrlichiae have been identified based on their reactivity with immune sera from human patients and animals. These include the major outer membrane proteins, ankyrin repeat proteins and tandem repeat proteins (TRP). Polyclonal antibodies directed against the tandem repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…A DNA vaccine targeting a p28 outer membrane protein homolog (MAP1) in another Ehrlichia species, E. ruminantium, also confers partial protection against infection challenges (16). Similarly, recent studies described that p28 outer membrane proteins of E. muris stimulate mouse memory B and T cell responses, reducing the bacterial burden after 10 to 14 days postchallenge with wild-type infection (17,18). Several studies of Ehrlichia species also demonstrated that attenuated strains offer a high level of protection.…”
mentioning
confidence: 99%
“…A DNA vaccine targeting a p28 outer membrane protein homolog (MAP1) in another Ehrlichia species, E. ruminantium, also confers partial protection against infection challenges (16). Similarly, recent studies described that p28 outer membrane proteins of E. muris stimulate mouse memory B and T cell responses, reducing the bacterial burden after 10 to 14 days postchallenge with wild-type infection (17,18). Several studies of Ehrlichia species also demonstrated that attenuated strains offer a high level of protection.…”
mentioning
confidence: 99%
“…In this study, two animal models were used: mouse-intraperitoneal inoculation and dog-tick transmission models. Although the mouse infection model is unnatural, most vaccine studies on vector-borne obligatory intracellular bacteria have been carried out in mice challenged by needle inoculation ( 54 ) and almost all Ehrlichia pathogenesis and immunologic research used this model to derive immunologic or other signatures of responses ( 55 58 ). Dog-tick transmission is the natural mode of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Other Ehrlichia immune-reactive identified antigens include ferric ion-binding protein, disulfide bond formation protein, ankyrin repeat proteins (i.e., E. canis gp200), and tandem repeat proteins (TRP-) [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Several orthologs of TRPs have been discovered in E. chaffeensis and E. canis —for example, TRP120/TRP140, TRP75/TRP95, TRP47/TRP36 and TRP32/TRP19 [ 40 ]. Through interaction with several host proteins, TRPs contribute to the infection establishment.…”
Section: Adaptive Immune Response To Antigens Derived From Tick-trmentioning
confidence: 99%
“…A recently identified E. muris TRP, P29, recognized as the ortholog E. chaffeensis TRP47 and E. canis TRP36, was found to generate a strong IgG antibody response and to stimulate CD4 + T cell differentiation into IFN-γ-producing Th1 effector/memory cells, activating macrophage microbicide activity. These effects suggest a possible inclusion for E. muris P29 in a subunit vaccine against ehrlichiosis [ 40 ].…”
Section: Adaptive Immune Response To Antigens Derived From Tick-trmentioning
confidence: 99%